Making Custodians: A design anthropology approach to designing emotionally enduring built environment artefacts - Forlano, Penelope (Curtin University, 2018)
My doctoral research through creative production takes a Design Anthropology approach to examine the person-object relationship typical of artefacts with long-term attachment and significance. I then speculate on the implications of these findings with the goal of designing enduring new built environment artefacts, surfaces, and furniture. The exegesis explores the context of this enquiry within design theory and practice and its significance, given the environmental impact of high levels of premature disposal and ‘fast’ consumption.